2022
DOI: 10.37231/jmtp.2022.3.2.222
|View full text |Cite
|
Sign up to set email alerts
|

Pandemic to Endemic: A Review of Key Enablers of Small Medium Enterprise Resilience

Abstract: The existence of various COVID-19 variants from Delta to Omicron has led to speculation that the spreading of the virus will continue; hence, the endless battle to fight it persists. The uncertainties in its progress from pandemic to endemic, renders it necessary to understand the applied mitigation and adaptation strategies amongst SMEs to build their future resilience as they are vulnerable and have limited resources. This study aims to develop a conceptual framework of the key enablers of SMEs’ resilience d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 0 publications
2
4
0
Order By: Relevance
“…These finding are consistent with the previous study by Ahmad et al (2019) on the positive and significant influence of economic empowerment towards the effectiveness of microfinance programmes in alleviating the well-being of women MSME entrepreneurs. Moreover, these results corroborate the earlier findings by Sri Rahayu et al (2023), Mohammad et al (2022), Hamdan et al (2021), and Che Omar et al (2020) on the need for digital empowerment for MSME entrepreneurs during the COVID-19 pandemic. Meanwhile, the social empowerment factor is negative and significant at 1%.…”
Section: Empirical Assessmentsupporting
confidence: 91%
See 4 more Smart Citations
“…These finding are consistent with the previous study by Ahmad et al (2019) on the positive and significant influence of economic empowerment towards the effectiveness of microfinance programmes in alleviating the well-being of women MSME entrepreneurs. Moreover, these results corroborate the earlier findings by Sri Rahayu et al (2023), Mohammad et al (2022), Hamdan et al (2021), and Che Omar et al (2020) on the need for digital empowerment for MSME entrepreneurs during the COVID-19 pandemic. Meanwhile, the social empowerment factor is negative and significant at 1%.…”
Section: Empirical Assessmentsupporting
confidence: 91%
“…It was found that microfinance facilities significantly and positively affect the borrower's household income and personal asset ownership. Furthermore, to overcome COVID-19 pandemic challenges, various assistance programmes were formulated by the Malaysian government, like the PRIHATIN package, to empower MSME entrepreneurs economically and financially (Mohammad et al 2022;Hamdan et al 2021;Che Omar et al 2020). Therefore, the first hypothesis statement of the study is the following: H 1 : There is a positive relationship between economic empowerment and the effectiveness of microfinance programmes.…”
Section: Economic Empowermentmentioning
confidence: 98%
See 3 more Smart Citations